Cleansing Nigeria’s Corrupt Bureaucracy: The Peril and Promise - Oyedele, Olanrewaju S.; Aluko, Opeyemi (Àgídìgbo: ABUAD Journal of the Humanities, 2018)
The Nigerian bureaucracy came under severe ridicule following the discovery and recovery of large-scale looting of government money and illicit assets by civil servants recently. The discoveries were made by the various federal government anticorruption Agencies such as the Economic and Financial Crimes Commission (EFCC), Independent Corrupt Practices Commission (ICPC) and the Code of Conduct Bureau (CCB). This is in spite of the Zero tolerance stance of the Mohammadu Buhari government for corruption in the civil service since it came to power about two year ago. Is it possible for a civil service bedevilled by this magnitude of corruption to be effective and efficient, especially in the area of national development? This paper holds the view that the government should ensure that its on-going efforts to cleanse the country’s civil service of the mess of corruption is intensified and pursued to the letter with the initiation of more stringent cleansing measures as well as providing adequate political will to crush the menace of corruption in the civil service.